2021
DOI: 10.3390/foods10020205
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Variation in Starch Content, Starch Granule Distribution and Starch Polymer Molecular Characteristics of French Bread Wheat

Abstract: This study investigates genetic and environmental variation in starch content and characteristics of 14 French bread cultivars. Understanding the impact of these factors on wheat quality is important for processors and especially bakers to maintain and meet the requirements of industrial specifications. Different traits were evaluated: starch content, distribution of starch granules, percentage of amylose and amylopectin and their molecular characteristics (weight-average molar mass, number-average molar mass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…Labuschagne et al [ 103 ] reported that the environment contributed the most to the protein and starch content, followed by the genotype for protein and the G×E interaction for starch content. Those results were recently confirmed in bread wheat [ 104 ]. In our study, the environment and the G×E interaction contributed the most to the variance of protein and starch content in both species, respectively.…”
Section: Discussionsupporting
confidence: 59%
“…Labuschagne et al [ 103 ] reported that the environment contributed the most to the protein and starch content, followed by the genotype for protein and the G×E interaction for starch content. Those results were recently confirmed in bread wheat [ 104 ]. In our study, the environment and the G×E interaction contributed the most to the variance of protein and starch content in both species, respectively.…”
Section: Discussionsupporting
confidence: 59%
“…[6] Starch is a natural polysaccharide with high functionality due to the presence of both amylose and amylopectin. [7] Hydroxyl groups in amylose and amylopectin of starch have the capacity to attract water molecules through hydrogen bonding. Starch finds limited applications in composite and packaging sectors due to its poor mechanical and water resistance properties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rhazi et al reported for wheat starch large deviations in weight average MM of the AP (weight average molar mass of amylopectin fraction [M w AP]) ranging from 10.4 to 58.4 × 10 6 g mol −1 and M w AM ranging from 1.4 to 13.8 × 10 5 g mol −1 . [58] However, the study included special waxy-or amyl-wheat (high AM wheat starch) cultivars so that AM levels varied between 17% and 41% w/w. [58] Lee et al examined rice starch cultivars which had also similar AM content and large differences in M w AP and M w AM values.…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…[58] However, the study included special waxy-or amyl-wheat (high AM wheat starch) cultivars so that AM levels varied between 17% and 41% w/w. [58] Lee et al examined rice starch cultivars which had also similar AM content and large differences in M w AP and M w AM values. [59] Interestingly, the different rice starches had also significantly different pasting properties analyzed with differential scanning calorimeter (DSC) and Rapid Visco Analyzer (RVA).…”
Section: Molecular Characterizationmentioning
confidence: 99%